Role of bovine herpesvirus type 5 (BoHV-5) in diseases of cattle. Recent findings on BoHV-5 association with genital disease - Favier, Paula Ariela (2012)
Bovine herpesvirus type 5 (BoHV-5) belongs to the family Herpesviridae, subfamily Alphaherpesvirinae, genus Varicellovirus. This virus is a major causative agent of non-suppurative meningoencephalitis in young cattle. It was first isolated in 1962 from a neurological disease outbreak in Australia. BoHV-5 is genetically and antigenically related to bovine herpesvirus type 1 (BoHV-1), a highly prevalent virus responsible for respiratory and genital disease in cattle. Initially, BoHV-5 was considered a subtype of BoHV-1 (BoHV-1.3). However, the exclusive presentation of outbreaks of neurological disease suggested that the virus was a new agent with characteristics of neuropathogenicity. Even though both are neurotropic viruses, only BoHV-5 is capable of replicating extensively in the central nervous system and inducing neurological disease. Occasionally, encephalitis caused by BoHV-1 has been reported. Like other alpha-herpesviruses, BoHV-5 can establish latency in nervous ganglia and, by stress factors or glucocorticoid treatment, latent virus can be reactivated. During episodes of reactivation, the virus is excreted in nasal, ocular and genital secretions and transmitted to other susceptible hosts. Recently, BoHV-5 has been associated with infection of the reproductive tract. The virus has been isolated and the presence of viral DNA has been demonstrated in semen samples from Brazil and Australia and natural transmission of the virus through contaminated semen has also been described. Embryos and oocytes are permissive for BoHV-5 infection and BoHV-5 DNA has been detected in the central nervous system of aborted fetuses. The objective of this review is to compile the limited information on the recent association between BoHV-5 and reproductive disorders in cattle.